REINTERPRETASI SURAH AL-AHZAB AYAT 33 PERSPEKTIF TAFSIR MAQASHIDI - Sulhadi, Asep; Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2023)
Islam as a religion that is rahmatan lil ‘alamin, the teachings contained therein inspire justice values, peace, humanity, equality and civilization. Therefore, if there is a conflicting understanding with islamic values above, so this understanding must be updated and reviewed. Among the religious texts that need to be reviewed are the verses of the Qur’an which textually contain misogynistic elements including Surah al-Ahzab verse 33. This verse is used by some circles as an argument to curb woman not to do activities outside the home. So that, the role of woman in the public sphere and social sphere become very limited or even nonexistent. This in the next round cause emergence to assumptions that Islamic teachings contain the discriminatory elements and gender bias. Whereas, Islam since the beginning of its presence, the Islamic teachings confirm that role discrimination and gender bias is a human rights violations must be eliminated. The purpose of this research is to review how interpretation of Surah al-Ahzab verse 33 associated with the current context by looking at the deepest intent dan purpose of the verse. This is of course important not only to fending off thought that tend to be rigid, eliminate negative accusations against the Islamic religion, but also to reaffirmed that Islam highly respects the justice values, peace, humanity, equality and civilization. The method that the author uses is descriptive analysis method, by using the maqashidi interpretation approach as an analytical knife to understand the meaning and intent of the verse above. By using the maqashidi interpretation approach, we can understand that the intent, purpose and benefit of the verse above is for the sake of role model, safety and security. The verse above is no way intended to demean, marginalize, discriminate against or restrain woman. But on the contrary, the verse above is actually a form of protection, respect, affection and glorification of woman. Keywords: Misogynistic, al-Ahzab verse 33, maqashidi interpretation